2022
DOI: 10.1002/ptr.7690
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of hawthorn leaf flavonoids in 25–35‐induced Alzheimer's disease model

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by β‐amyloid (Aβ) plaques, neurofibrillary tangles, neuronal cell loss, and oxidative stress. Further deposition of Aβ in the brain induces oxidative stress, neuroinflammation, and memory dysfunction. Hawthorn (Crataegus pinnatifida Bge.) leaf, a known traditional Chinese medicine, is commonly used for the treatment of hyperlipidemia, heart palpitations, forgetfulness, and tinnitus, and its main bioactive components are Hawthorn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 123 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…HLF was administered at doses of 50, 100, and 200 mg/kg for a period of 30 days and showed a significant improvement in neuronal damage and memory deficits, an increase in the activity and levels of the antioxidant enzymes SOD, CAT, and GSH, and a decrease in MDA. HLF reduced oxidative stress specifically through activation of the NRF2/ARE signaling pathway ( 107 ).…”
Section: Phytochemical Antioxidant Compounds That Act As Activators O...mentioning
confidence: 99%
“…HLF was administered at doses of 50, 100, and 200 mg/kg for a period of 30 days and showed a significant improvement in neuronal damage and memory deficits, an increase in the activity and levels of the antioxidant enzymes SOD, CAT, and GSH, and a decrease in MDA. HLF reduced oxidative stress specifically through activation of the NRF2/ARE signaling pathway ( 107 ).…”
Section: Phytochemical Antioxidant Compounds That Act As Activators O...mentioning
confidence: 99%
“…[1], with the effects of activating blood flow and removing blood stasis [2][3][4][5]. Hawthorn leaf extract is a liquid obtained by extracting hawthorn leaf powder with 50% ethanol and elution with D101 macroporous resin or extracted by ultrasonic extraction after adding 60% methanol [6][7][8]. It has been reported that hawthorn leaf extract can reduce blood plasma viscosity, promote hemoglobin degradation, and increase the number of platelets to possess therapeutic effects on the cardiovascular systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…The extract is a complex multicomponent system including flavonoids, sterols, terpenes, organic acids, etc. ; flavonoids are the main active ingredients [4,7,8].…”
Section: Introductionmentioning
confidence: 99%